Pengaruh Efikasi Diri dan Etos Kerja Islam terhadap Kinerja Guru pada Madrasah Tsanawiyah - Khotimah, Husnul; Wibowo, Ugung DA (PSIMPHONI, 2022)
Teachers play a crucial role as role models for their students, requiring a blend of strong personality traits, engaging performance, high quality, and competence to effectively guide their students. This study investigated the impact of self-efficacy and Islamic work ethic on teacher performance at Madrasah Tsanawiyah in Purbalingga Regency. It was hypothesized that both self-efficacy and Islamic work ethic significantly influence teacher performance in this setting. Employing a quantitative approach, the study surveyed 155 teachers from Madrasah Tsanawiyah in Purbalingga, using scales to measure performance, self-efficacy, and Islamic work ethic. The results indicated that self-efficacy and Islamic work ethic have a significant effect on teacher performance, explaining 78.2% of the variance, with 21.8% attributed to other factors. These findings underscore the importance of fostering self-efficacy and reinforcing Islamic work ethics among teachers to enhance their performance. Educational policymakers and school administrators should consider implementing professional development programs focused on building self-efficacy and integrating Islamic work ethics into teacher training.